Development and application of dedicated positron emission tomography (PET) systems in prostate cancer diagnostics - Mateusz Wędrowski; Marta Maruszak; Ewelina Wędrowska; Elżbieta Piskorska; Bogdan Małkowski (Kazimierz Wielki University, 2017)
Introduction: One of the most important parameter in prostate cancer diagnostics is fast and accurate diagnosis. The important role plays finding cancer markers in blood but also advanced medical imaging systems technology, that allows for faster and more efficient objects projection. There are ongoing efforts to develop new multimodal imaging systems and find new PET radiopharmaceuticals. Aim of the study: The aim of this study is presentation of chosen information about dedicated PET systems in fusion with US and description of the most important PET radiopharmaceuticals for prostate cancer diagnosis that could confirm the meaning of new imaging technologies. Short description of state of knowledge: The most interesting recent scientific trends in prostate cancer medical imaging is presented in this work. Discussion is based on grant projects under realization. Potential clinical application problems were analyzed. The motivation of these projects was explained. Advantages and drawbacks of most recent radiopharmaceuticals for prostate cancer diagnosis was also discussed. Summation: New ideas in prostate cancer therapy are based on replacement the blind biopsy with guided biopsy in new meaning. Advanced medical imaging technology and application of new PET radiotracers in Poland (- the country with high ageing factor) may allow for cancer slowdown in early stage and minimize the treatment costs.